LINC01322 may serve as a potential diagnostic marker for advanced stage tumors in renal cell carcinoma patients eligible for total nephrectomy - Amirhosein Maharati; Negin Taghehchian; Fatemeh Taghavinia; Alireza Golshan; Azadeh Aarabi; Mohammad Reza Abbaszadegan; Meysam Moghbeli (Biochemistry and Biophysics Reports, 2024)
Background: Renal cell carcinoma (RCC) is a common urological cancer globally and shows a favorable prognosis in early stages of the tumor progression. Due to the poor prognosis for metastatic RCC patients, it is crucial to explore the molecular biology of RCC progression to establish efficient diagnostic and therapeutic markers for these patients. Long non-coding RNAs (lncRNAs) have critical roles in regulation of tumor cell proliferation, migration, and apoptosis during RCC progression. For the first time in the present study, we assessed the LINC01322 RNA expression levels in RCC patients to introduce that as a potential tumor marker among these patients. Methods: we visualized LINC01322 expression data using the online tool Gene Expression Profiling Interactive Analysis (GEPIA2) across different cancers and normal tissues. Fifty fresh samples of RCC tumor tissues and their adjacent normal margins were collected to analyze the RNA expression of LINC01322 and its association with the clinicopathological features of RCC patients. The SYBR green method was used in real-time PCR to measure the LINC01322 RNA expression levels in RCC patients. Results: Based on in-silico analysis, we hypothesized that LINC01322 could be involved in RCC progression by interacting with VHL, thereby influencing the tumor microenvironment. There were significant increased levels of LINC01322 RNA expressions in advanced stage compared with primary stage tumors that were located in left kidney (p = 0.048). Left kidney that were undergone the total nephrectomy had significant higher levels of LINC01322 RNA expressions compared with tumors in right kidney (p = 0.045). There was a direct correlation between the levels of LINC01322 RNA expression and RCC tumor size. Conclusions: considering the substantial increase in LINC01322 RNA expression in advanced stage RCC tumors that are candidates for total nephrectomy; it could be suggested as a potential diagnostic indicator for high-risk patients. In-silico analysis also revealed that LINC01322 could be involved in regulation of tumor microenvironment during RCC progression by interacting with VHL. However, further investigations are needed to validate the potential link between LINC01322 and VHL during RCC progression. Evaluating the serum LINC01322 RNA levels in RCC patients is also necessary to use that as a diagnostic marker in clinical settings.